(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
School education is an important segment of the total educational system contributing significantly to the individual as well as to national development. A good school provides environment conducive for development of cognitive, affective and psychomotor domains for all round development of individuals.